(3OjhGf YeGQI Gdjefjs - (3YeGQI Gdjefj , YeGQI Hf Ydj Hf RjOGf GdMcej GdePMLj Gdjefj, fLe GdOjf CHh eMeO,J (B569 (3g` s
(3ChdgG (B:s
(3eHJhQ, jHJOj CKfGA bGajg GdgeRI Hbhdg(B: (3hGdHQb jTgO hGdQhGYO CfgG YfhGf cd SMGHg hWaGA s
(3BNQgG (B:s
(3ef bGajg GdjGA QVjJ HGdcJH HYO GdbQH hGfbWYJ MJi QVjJ SdGekG aj MhGTjgG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B29 - (3U(B227s
(3bHd GdOjhGf YOI bUGFO HMcGjGJgG efgG YjfjI GHf RQjbs
(3haj BNQ GdOjhGf YOI ebWYGJ dHYV GdTYQGA hde ojSeYges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B193s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B164 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs